Research on the Theoretical Mechanism and Industrial Model of Digital Economy Empowering China's Silver Economy (Journal of economic and management development research, 2026)
At present, the process of population aging in China is accelerating continuously, and the structural contradiction between the consumption demand of the elderly group and market supply has become increasingly prominent. Developing the old-age economy is not only an inevitable choice to respond to the aging challenge, but also an important starting point for cultivating new economic growth points. Relying on information technologies such as big data and cloud computing as well as platform carriers, the digital economy provides a new path for the old-age economy to break through the bottlenecks of traditional development. Based on the core categories of digital consumption and digital services, starting from the technical characteristics and value logic of the digital economy, this paper explores the internal mechanism of its empowerment to the old-age economy, analyzes the direction of the reconstruction of the old-age economy's industrial model from the perspective of the digital economy, and proposes to promote the transformation of the old-age economy from a "material supply-oriented" model to a "material and digital service collaborative-oriented" model through the upgrading of scenario digitalization, service personalization and value diversification, so as to provide theoretical reference and logical support for the high-quality development of China's old-age economy.
Keywords: Digital economy; Old-age economy; Enabling mechanism; Industrial model; Population aging